The four dimensions of the Environmental Tourism Carrying Capacity (ETCC) model at Royal Belum State Park, Malaysia - Mohd. Din, Shamzani Affendy; Abdullah, Alias; Mohd Nayan, Noorul Iffa; Osman, Sharina (Taylor's University Sdn Bhd, 2021)
The Environmental Tourism Carrying Capacity (ETCC) is a location-specific implementation model, where metrics are built rather than generalised for all sites, to solve problems that arise on-site. This analysis determines the suitability of certain indicators over others to establish a hierarchical structure of ETCC for Royal Belum State Park (RBSP). The approach used in this research is triangulation that involves a process of defining relevant indicators through a content analysis and evaluating these indicators indicators through a questionnaire survey. The Microsoft Excel software was used to evaluate the data gathered to identify the relevant indicators for RBSP. The study found that all respondents acknowledged the four dimensions of the ETCC model: biophysical environment, social-cultural, political-economics, and management of tourism facilities. The most important variables for the Biophysical Environment dimension are water management, waste management and air pollution whereas, the highest favoured predictors for the social-cultural component are moral action tolerance and crime. Public income and contributions earned were highly rated for the political-economics dimension. Finally, the top three tourism facilities preferred are implementation of strict intrusion protection rules, good scenic quality, and interesting activities on offer. This study also proved that through an assessment of significant indicators developed for a specific site, the ETCC model could be a huge success depending on the encountered issues and problems.